AB1394 Compliance and arthralgias in clinical therapy (compact): Assessment of the incidence of arthralgia, therapy costs and compliance within the first year of anastrozole therapy. (23rd January 2014) - Bolten, W.W.; Blettner, M.; Harbeck, N.; Hindenburg, H.-J.; Jackisch, C.; Klein, P.; König, K.; Rief, W.; Wallwiener, D.; Zaun, S.; Kreienberg, R.; Hadji, P.
Abstract : Background: Aromatase inhibitors (AI) are well established as adjuvant endocrine treatment for postmenopausal women with hormone receptor-positive (HR+) early breast cancer (EBC). Drug-induced myalgia or arthralgia is among the most frequently reported adverse drug reactions to AIs. Objectives: Little is known about the pathomechanism by which AIs cause muscle and joint injury. The literature on skeletal muscle complaints with AIs is confusing, in part because of a lack of clear definitions. Myalgia/arthralgia is defined as muscle/joint pain and is likely to affect patients' quality of life and compliance with AI medication . We designed a prospective trial to collect real world data on the effects of AI-associated myalgia or arthralgia on patient compliance, patient outcomes as well as treatment costs of myalgia or arthralgia. Methods: COMPACT is an open, prospective, non-interventional study (NCT00857012 ) assessing the incidence of arthralgia, therapy costs, and compliance within the first year of adjuvant anastrozole therapy in postmenopausal patients with HR+ EBC. The study is sponsored by AstraZeneca and supported by German health insurance funds. Patients on adjuvant AI anastrozole for 3-6 months were enrolled and stratified by initial adjuvant anastrozole or switch from tamoxifen. All patients receive regular standardized information about breast cancer from baseline to week 20 after study start to support treatment compliance. Data on demographics, arthralgias, therapy of arthralgia and quality of life are collected at baseline, 3, 6 and 9 months. Primary endpoints are scaled data on arthralgia and compliance within the first year of AI therapy. Secondary endpoints include the incidence of arthralgias, therapy costs, reasons for non-compliance, and influence of arthralgias on clinical outcome. For a subgroup of patients data on arthralgia therapy and compliance will be validated with corresponding accounting data of participating health insurance funds. Results: From April 2009 to March 2011, 2313 patients were recruited, 2007 receiving upfront anastrozole and 306 patients on switch therapy. Mean age was 64.5 years, mean BMI 27.7. 41.5% of patients had concomitant symptoms relating to skeleton or musculature, and 11.9% stated arthralgias existing prior to AI-treatment. 13.1% reported a worsening of preexisting arthralgias or new arthralgia after starting AI. All patients will be followed for arthralgia, arthralgia treatment, and compliance to therapy. Conclusions: COMPACT aims to provide valid data on AI-associated arthralgias, treatment, therapy compliance and treatment costs. This may help to better inform patients and health care providers about these clinically important issues with the aim to improve adherence to AI-treatment, breast cancer outcomes, and therapy costs. Disclosure of Interest: W. Bolten Consultant for: AstraZeneca, M. Blettner: None Declared, N. Harbeck Consultant for: member of study steering committee, H.-J. Hindenburg: None Declared, C. Jackisch: None Declared, P. Klein: None Declared, K. König: None Declared, W. Rief: None Declared, D. Wallwiener: None Declared, S. Zaun: None Declared, R. Kreienberg: None Declared, P. Hadji Consultant for: AstraZeneca